FACTORS AFFECTING TURNOVER INTENTION: THE MEDIATING ROLE OF JOB BURNOUT - Talitha Rania; Unggul Kustiawan (Journal of Applied Economics in Developing Countries, 2025)
High turnover intention is a crucial challenge in human resource management, particularly in the outsourcing sector in the industrial area of Tangerang Regency. This study examines the influence of perceived organisational support, job insecurity, emotional intelligence, and work-family conflict on turnover intention through the mediation of job burnout. This quantitative study involved 300 outsourcing employees with a minimum of one year of service. Data were analysed using Structural Equation Modelling-Partial Least Squares (SEM-PLS) with SmartPLS 4 software. The results showed that all variables studied had a positive influence on job burnout and turnover intention. Job burnout was found to act as a significant mediator between the four independent variables and turnover intention. These findings underscore the importance of addressing perceived organisational support, job insecurity, work-family conflict, and emotional intelligence in managing burnout and minimising employees' desire to resign. The study provides practical insights for outsourcing company management to create a supportive work environment and develop employees' soft skills to enhance organisational productivity.